2015
DOI: 10.1007/s10900-014-9988-6
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of Poverty and Health Outcomes Among People Living with HIV Infection: Limited Resources and Competing Needs

Abstract: HIV infection is concentrated in populations living in poverty. We examined the overlapping and independent effects of multiple poverty indicators on HIV-related health status. Because substance use can create competing survival needs when resources are limited, we also sought to objectively measure expenditures on food relative to alcohol and tobacco products. To achieve these aims, 459 men and 212 women living with HIV infection in Atlanta, GA completed measures of socio-demographic and heath characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 20 publications
(21 reference statements)
0
23
0
Order By: Relevance
“…Spatial variation in routine and prevention behaviors, which tended to spatially overlap in this study, could be limited by recently moving to town or by transportation access (Dasgupta et al, 2015; Kalichman et al, 2015). However, as a key component of this categorization of activity space, spatial variation in an individual’s potential sexual risk behaviors may especially be shaped by individual, rather than geographic, factors.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Spatial variation in routine and prevention behaviors, which tended to spatially overlap in this study, could be limited by recently moving to town or by transportation access (Dasgupta et al, 2015; Kalichman et al, 2015). However, as a key component of this categorization of activity space, spatial variation in an individual’s potential sexual risk behaviors may especially be shaped by individual, rather than geographic, factors.…”
Section: Discussionmentioning
confidence: 91%
“…Patterns of associations between the activity space classes and this combined measure may reflect difference in both the spatial distribution and accessibility of locations where prevention and sexual risk may occur, including HIV testing, HIV treatment, and locations where MSM congregate. High poverty, average density areas of MSAs may have less availability of testing and prevention resources and men may have less access to those resources (Dasgupta et al, 2015; Kalichman et al, 2015), providing one possible explanation of a spatially restricted activity space. Men living in these high poverty, average density areas were also more likely to be members of an activity space class with local, rather than diverse, sexual risk, possibly due to the spatial distribution of MSM and limited locations where MSM may gather (Delaney et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However, the non-significant effects for these substances may be due to different reference periods for use and no information on the frequency and duration of use. These are important considerations as a recent study in an HIV-positive population in the United States found that those who use tobacco and alcohol may use up to one-quarter of their financial resources on these substances [43]. As shown in Table 1, the majority of food insecure participants used marijuana, cigarettes, and also consumed alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The majority (67%) of papers did not explain their selection of alcohol measures. A minority (19%) presented a justification based on general population psychometric performance of the measure (Kalichman et al, 2015; Newcomb et al, 2012; Stewart et al, 2015); the established relationship of a variable with a study outcome (Sun et al, 2016); compatibility with a larger study (Reisner et al, 2013); or characteristics of the study population other than sex and gender (Bryan et al, 2017; Ebersole et al, 2012; Huebner et al, 2015). Strikingly absent from any papers was consideration of gender as a social factor that may shape alcohol outcomes, especially through mediating variables such as alcohol stigma and group norms.…”
Section: Review Of Current Researchmentioning
confidence: 99%